Fertilizer application and Non-Point Source Pollution problems between Uganda and China-Review - Natamba, Leo; Weihua, Zhang; Sissoko, Founemakan (Advances in Social Sciences Research Journal, 2016)
Non-point source pollution comes from diffuse sources in the environment primarily from agricultural areas draining water into a river, lake or sea. It is not only a problem to China but also many other countries in the world. Africa and in particular Uganda faces a similar problem but the extent needs to be ascertained. China’s use of fertilizers and pesticides to boost food production stems back from 1970’s. Uganda however has not yet reached at the level of using massive agricultural inputs. NPSP poses a big threat not only to the water habitats but also to the lives of people who depend on water from different surface water sources. This review paper looks at the current state of Uganda and China’s surface water situation, water ecology, and areas severely affected by the problem, water use of China’s major rivers and proposes policy intervention that the government can take in controlling the problem that if left with little or no attention can put the health of people and other users in a dire state. It also looks at Uganda’s fertilizer situation in the East African region and lessons to learn from fertilizer heavy users like China to avoid similar problems. China’s government has committed a great deal of resources in trying to control the problem but there is a lot that is still needed to take a reasonable stride to counteract the challenges that result from the problem among which may include extension education to rural farmers and other key stakeholders.